Early Aggressive Hydration Hastens Clinical Improvement in Mild Acute Pancreatitis. (May 2017) - Buxbaum, James L; Quezada, Michael; Da, Ben; Jani, Niraj; Lane, Christianne; Mwengela, Didi; Kelly, Thomas; Jhun, Paul; Dhanireddy, Kiran; Laine, Loren
Abstract : Objectives: Early aggressive intravenous hydration is recommended for acute pancreatitis treatment although randomized trials have not documented benefit. We performed a randomized trial of aggressive vs. standard hydration in the initial management of mild acute pancreatitis. Methods: Sixty patients with acute pancreatitis without systemic inflammatory response syndrome (SIRS) or organ failure were randomized within 4 h of diagnosis to aggressive (20 ml/kg bolus followed by 3 ml/kg/h) vs. standard (10 ml/kg bolus followed by 1.5 mg/kg/h) hydration with Lactated Ringer's solution. Patients were assessed at 12‐h intervals. At each interval, in both groups, if hematocrit, blood urea nitrogen (BUN), or creatinine was increased, a bolus of 20 ml/kg followed by 3 ml/kg/h was given; if labs were decreased and epigastric pain was decreased (measured on 0–10 visual analog scale), hydration was then given at 1.5 ml/kg/h and clear liquid diet was started. The primary endpoint, clinical improvement within 36 h, was defined as the combination of decreased hematocrit, BUN, and creatinine; improved pain; and tolerance of oral diet. Results: The mean age of the patients was 45 years and only 14 (23%) had comorbidities. A higher proportion of patients treated with aggressive vs. standard hydration showed clinical improvement at 36 h: 70 vs. 42% ( P =0.03). The rate of clinical improvement was greater with aggressive vs. standard hydration by Cox regression analysis: adjusted hazard ratio=2.32, 95% confidence interval 1.21–4.45. Persistent SIRS occurred less commonly with aggressive hydration (7.4 vs. 21.1%; adjusted odds ratio (OR)=0.12, 0.02–0.94) as did hemoconcentration (11.1 vs. 36.4%, adjusted OR=0.08, 0.01–0.49). No patients developed signs of volume overload. Conclusions: Early aggressive intravenous hydration with Lactated Ringer's solution hastens clinical improvement in patients with mild acute pancreatitis.